Optimalisasi Penegakan Hukum Terhadap Penyelenggaraan Peradilan Melalui E-Court Dalam Mewujudkan Keadilan Bagi Masyarakat Di Era Digitalisasi - Vivi Lutfia (Lex Renaissance, 2021)
The initial construction of the research was based on the digitization process in the judiciary which has presented E-Court as an effort to create effectiveness and efficiency for justice in society. Based on this premise, the author endeavors to explore the existence of E-Court with Article 2 paragraph (4) of Law Number 48 of 2009 concerning Judicial Power in which justice is carried out on the principle of simple, fast, and low cost. The principle of the administration of justice is then confronted with the concept of law enforcement. The objectives of this study are, first, to analyze the administration of justice in Indonesia in the digitalization era; second, knowing the E-Court law enforcement instrument in the administration of justice in Indonesia. This research is a normative legal research using the Statute Approach and Conceptual Approach. The results of the study conclude, first, that the administration of justice in Indonesia is still characterized by problems of court administration and the high cost of access to justice. Second, in the digitalization era, E-Court law enforcement instruments include: legally the substance of E-Court regulation still needs to be perfected. In a legal structure, human resources need to be empowered. In legal culture, the position of E-Court is basically parallel to technological developments that are common in society, but psychologically, people still need to adapt to the E-Court system. In terms of legal infrastructure, some E-Court accessibility is still constrained by facilities and infrastructure.Keywords: E-court; legal enforcement; the principle of judicial administrationAbstrakKonstruksi awal penelitian didasarkan pada proses digitalisasi di ranah peradilan yang telah menghadirkan E-Court sebagai upaya menciptakan efektifitas dan efisiensi demi keadilan di masyarakat. Berpijak pada premis ini, penulis berikhtiar untuk mengeksplorasi eksistensi E-Court dengan Pasal 2 ayat (4) Undang-Undang Nomor 48 Tahun 2009 tentang Kekuasaan Kehakiman di mana peradilan dilakukan dengan asas sederhana, cepat, dan biaya ringan. Asas penyelenggaraan peradilan tersebut kemudian dihadapkan dengan konsep penegakan hukum. Tujuan penelitian ini yaitu, pertama, menganalisis penyelenggaraan peradilan di Indonesia di era digitalisasi; kedua, mengetahui instrumen penegakan hukum E-Court dalam penyelenggaraan peradilan di Indonesia. Penelitian ini merupakan penelitian hukum normatif dengan metode Statute Approach dan Conseptual Approach. Hasil Penelitian menyimpulkan, pertama, penyelenggraan peradilan di Indonesia masih diwarnai persoalan administrasi pengadilan hingga mahalnya akses untuk mencapai keadilan. Kedua, di era digitaliasi, instrumen penegakan hukum E-Court mencakup: secara legal substance pengaturan E-Court masih perlu untuk disempurnakan. Secara legal structure, sumber daya manusia perlu diberdayakan. Secara legal culture, kedudukan E-Court pada dasarnya sejajar dengan perkembangan teknologi yang lazim di masyarakat, namun secara psikologis masyarakat masih perlu beradaptasi dengan sistem E-Court. Dari segi legal infrastructure, sebagian aksesibilitas E-Court masih terkendala sarana dan prasarana.Kata Kunci: E-Court; asas penyelenggaraan peradilan; penegakan hukum